Fish in habitats with higher motorboat disturbance show reduced sensitivity to motorboat noise. (31st October 2018) - Harding, Harry R.; Gordon, Timothy A. C.; Hsuan, Rachel E.; Mackaness, Alex C. E.; Radford, Andrew N.; Simpson, Stephen D.
Abstract : Anthropogenic noise can negatively impact many taxa worldwide. It is possible that in noisy, high-disturbance environments, the range and severity of impacts could diminish over time, but the influence of previous disturbance remains untested in natural conditions. This study demonstrates the effects of motorboat noise on the physiology of an endemic cichlid fish in Lake Malawi. Exposure to motorboats (driven 20–100 m from fish) and loudspeaker playback of motorboat noise both elevated the oxygen-consumption rate at a single lower-disturbance site, characterized by low historic and current motorboat activity. Repeating this assay at further lower-disturbance sites revealed a consistent effect of elevated oxygen consumption in response to motorboat disturbance. However, when similar trials were repeated at four higher-disturbance sites, no effect of motorboat exposure was detected. These results demonstrate that disturbance history can affect local population responses to noise. Action regarding noise pollution should consider the past, as well as the present, when planning for the future.